Complement Alternative and Mannose-Binding Lectin Pathway Activation Is Associated With COVID-19 Mortality - Defendi, Federica; Leroy, Corentin; Epaulard, Olivier; Clavarino, Giovanna; Vilotitch, Antoine; Le Marechal, Marion; Jacob, Marie-Christine; Raskovalova, Tatiana; Pernollet, Martine; Le Gouellec, Audrey; Bosson, Jean-Luc; Poignard, Pascal; et al. (Frontiers in Immunology, 2021)
Background: The SARS-CoV-2 infection triggers excessive immune response resulting in increased levels of pro-inflammatory cytokines, endothelial injury and intravascular coagulopathy. The complement system (CS) activation participates to this hyperinflammatory response. However, it is still unclear which activation pathways (classical, alternative or lectin pathway) pilots the effector mechanisms that contribute to critical illness. To better understand the immune correlates of disease severity, we performed an analysis of CS activation pathways and components in samples collected from COVID-19 patients hospitalized in Grenoble Alpes University Hospital between 1 and 30 April 2020 and of their relationship with the clinical outcomes. Methods: We conducted a retrospective, single-center study cohort in 74 hospitalized patients with RT-PCR-proven COVID-19. The functional activities of classical, alternative and mannose-binding lectin (MBL) pathways and the antigenic levels of the individual components C1q, C4, C3, C5, Factor B and MBL were measured in patients’ samples during hospital admission. Hierarchical clustering with the Ward method was performed in order to identify clusters of patients with similar characteristics of complement markers. Age was included in the model. Then, the clusters were compared with the patient clinical features: rate of intensive care unit (ICU) admission, corticoid treatment, oxygen requirement, mortality. Results: Four clusters were identified according to complement parameters. Among them, 2 clusters revealed remarkable profiles: in one cluster (n=15), patients exhibited activation of alternative and lectin pathways and low antigenic levels of MBL, C4, C3, Factor B and C5 compared to all the others clusters; this cluster had the higher proportion of patients who died (27%) and required oxygen support (80%) or ICU care (53%). In contrast, the second cluster (n=19) presented inflammatory profile with high classical pathway activity and antigenic levels of complement components; a low proportion of patients required ICU care (26%) and no patient died in this group. Conclusion: These findings argue in favor of prominent activation of the alternative and MBL complement pathways in severe COVID-19, but the spectrum of complement involvement seems to be heterogeneous requiring larger studies., supporting complement inhibitors as effective therapeutic option in COVID-19 patients.